2023
DOI: 10.1186/s13018-023-03516-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between C-reactive protein and postoperative mortality in patients undergoing hip fracture surgery: a meta-analysis

Abstract: Background Hip fracture is a common but devastating disease with a high mortality rate in the older adult population. C-reactive protein (CRP) is a predictor of the prognosis in many diseases, but its correlations with patient outcomes following hip fracture surgery remain unclear. In this meta-analysis, we investigated the correlation between perioperative CRP level and postoperative mortality in patients undergoing hip fracture surgery. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In rat models, systemic inflammation has been shown to be aggravated by hip fracture in aged animals [ 7 ]. Consistently, clinical studies have also demonstrated that inflammatory biomarkers such as TNF-α, IL-6, IL-10, and CRP may play an important role in postoperative mortality in elderly hip fracture patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 84%
“…In rat models, systemic inflammation has been shown to be aggravated by hip fracture in aged animals [ 7 ]. Consistently, clinical studies have also demonstrated that inflammatory biomarkers such as TNF-α, IL-6, IL-10, and CRP may play an important role in postoperative mortality in elderly hip fracture patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 84%
“…Given the projected global increase in hip fracture, addressing the substantial hip fracture-associated health risks of older adults is crucial (1). Numerous studies have identi ed a positive association between postoperative mortality and various in ammatory parameters related to hip fracture surgery, including RDW (11,(16)(17)(18)(19), NLR (6,11,16,20,21), PLR (16, 21-23), C-reactive protein level (24), albumin level (25), and total lymphocyte count (25). To date, no prospective study has compared single laboratory parameters as prognostic factors for the mortality risk associated with hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed a potential link between blood markers obtained via routine blood tests and hip fracture outcomes. Specifically, studies have reported that low hemoglobin, low albumin, high creatinine, and high C-reactive protein (CRP) were associated with a relatively high risk of death [ 9 , 10 ]. Moreover, red blood cell distribution width (RDW) has been identified as a probable predictor for mortality following hip fractures [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%